Metamotivational profiles of eating characteristics and body image in athletes - Culpepper, D. O.; Jevas, S.; Archer, K. J. (Research Quarterly for Exercise and Sport, 2009)
Purpose: Over the past 20 years, considerable scientific attention has been directed toward the potential role that sport involvement plays in athletes' development of attitudes and behaviors about disordered eating. It appears that athletes as a population self-report more eating disorder symptoms than do nonathletes (Zucker, Womble, Williamson, & Perrin, 1999). There has been an implicit expectation that certain types of athletes could be at risk for developing eating and dieting pathologies because of the specific task demands of their sport (Sundgot-Borgen, 1993). Judged sports such as gymnastics, diving, cheerleading, and dance place more importance on the individual's body appearance, which may lead to disordered eating among the competitors (Zucker, et al., 1999). Refereed sports such as basketball place a stronger emphasis on training and do not rely as much on body appearance; therefore athletes participating in these sports may be less likely to be associated with disordered eating patterns (Schwarz, et al., 2005). The purpose of this study was to determine 1) if personality and motivation influence body image and eating characteristics; 2) if a particular type of sport influences body image and eating characteristics; 3) if there is a difference among gender comparable and gender specific sports in regards to body image and eating characteristics.